The Mechanism of the Zika Virus Crossing the Placental Barrier and the Blood-Brain Barrier - Chiu, Chi-Fen; Chu, Li-Wei; Liao, I-Chen; Simanjuntak, Yogy; Lin, Yi-Ling; Juan, Chi-Chang; Ping, Yueh-Hsin (Frontiers in Microbiology, 2020)
Zika virus (ZIKV) infection causes severe neurological symptoms in adults and fetal microcephaly and the virus is detected in the brain of microcephaly and meningoencephalitis patient. However, the mechanism of ZIKV crossing the physiological barrier to the central nervous systems (CNS) remains elusive. The placental barrier and the blood brain barrier (BBB) protect the fetus from pathogens and ensure healthy brain development during pregnancy. In this study, we used human placenta trophoblasts cells (JEG-3) and human brain-derived endothelial cells (hCMEC/D3) as in vitro models of the physiological barriers. Results showed that ZIKV could infect JEG-3 cells effectively and reduce the amounts of ZO-1 and occludin between adjacent cells by the proteasomal degradation pathway, suggesting that the permeability of the barrier differentially changed in response to ZIKV infection, allowing the virus particle to cross the host barrier. In contrast, ZIKV could infect hCMEC/D3 cells without disrupting the BBB barrier permeability and tight junction protein expression. Although no disruption to the BBB was observed during ZIKV infection, ZIKV particles were released on the basal side of the BBB model and infected underlying cells. In addition, we observed that fluorescence-labeled ZIKV particles could cross the in vitro placenta barrier and blood brain barrier model by transcytosis and the action of transcytosis could be blocked by low temperature and pharmacological inhibitors of endocytosis. In summary, the ZIKV uses a cell-type specific paracellular pathway to cross the placenta monolayer barrier by disrupting cellular tight junction. In addition, the ZIKV can also cross both the placenta barrier and the BBB by transcytosis. Our study provided new insights into on the mechanism of the cellular barrier penetration of ZIKV particles.